Allelopathy and the active metabolites of the endophytic fungus, Alternaria J46, from Platycladus orientalis. Issue 3 (22nd June 2015) - Hao, Shuang‐Hong; Wei, Yan; Wang, Jing; Zhou, Yuan‐Ming
Abstract : The endophytic fungus, Alternaria J46, was isolated from the stem of the medicinal plant, Platycladus orientalis . A suspension of Alternaria J46 mycelial segments and the culture filtrates of the fungi exhibited marked seed germination inhibition against the monocot wheat, large crabgrass, bromegrass, rice and barnyardgrass and weak inhibition against the dicot redroot pigweed and morning glory, but it was safe for use on soybean, rape, cucumber, tomato, lettuce and radish crops. It is possible to use J46 culture filtrates in order to prevent monocot weeds in dicot cropland. Three active metabolites were isolated from an extract of the fungus cultures and elucidated as 3‐acetyl‐5‐ sec ‐butyltetramic acid (1, tenuazonic acid), 3‐acetyl‐5‐ iso ‐butyltetramic acid (2, vivotoxin II) and cyclo‐ (L‐leucyl‐L‐proline) (3). Among these three compounds, compounds 1 and 2 showed significant phytotoxic effects on the seed germination of large crabgrass, while compound 3 exhibited weak activity, and all were safe for lettuce at 100 μg mL −1 . Accordingly, compounds 1 and 2 were the main active metabolites that were responsible for endophytic fungus Alternaria J46's strong seed germination inhibition against monocotyledons.